Going pro-social: Extending the individual-venture nexus to the collective level - Branzei, Oana; Parker, Simon C.; Moroz, Peter W.; Gamble, Edward (Journal of Business Venturing, 2018)
The aim of this Special Issue is to demonstrate how drawing on multidisciplinary insights from the literature on prosociality can broaden the individual-opportunity nexus to make room for a variety of actors. Five feature articles emphasize the collective level of the analysis, underscoring the social distance between the entrepreneurs and the different communities they serve. Leveraging construal level theory, we abductively derive an organizing framework that helps us articulate how stretching or compressing social distance can transform initial opportunities into occasions for serving the greater good. We identify two distinct mechanisms present in all five empirical studies that explain how the needs and hopes of many others may add creativity, consistency and connectivity to one's venture. We also connect these abductive insights with the two editorials that follow this introduction and nudge our collective attention towards the research opportunities awaiting our academic community once we begin to relax the egocentric reference point that, until recently, has defined the discipline of entrepreneurship.